PENDIDIKAN KEWARGANEGARAAN DI SEKOLAH DASAR: Aplikasi Teori Emile Durkheim tentang Moralitas dan Pendidikan Moral - Eriyanti, Fitri (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2006)
Durkheim had a great attention to morality and moral education. He viewed that, as an institution, a school had an important role in moral education. In his opinion, the best time to implant morality to children is when they are in their childhood, especially when they are in elementary school. In Indonesia, moral education is included into Civic Education curricula. In the case of elementary school, the goal of this subject is emphasized on the implementation of moral values in daily lives. This article will elaborate the difference between the concept of Durkheim’s moral education and moral education implemented in Indonesia elementary schools. Kata kunci: Moralitas, Nilai Moral, Pendidikan Moral, Pendidikan Kewarganegaraan